The picture of the hispanics in U.S. mainstream media - Saiz Varona, Claudia (Univerzita Pardubice, 2008)
Guided by the principle of framing, this study explores the topics, themes, sources, and differences of the three major U.S. news magazines— Time, Newsweek, and U.S.News & World Report- over a year-long period and investigates whether they are fully and fairly telling the story of the Hispanic American experience.
Obraz hispánských američanů v amerických sdělovacích prostředcích
Keywords: Hispánci; americké tradiční sdělovací prostředky; imigrace; americké časopisy; Hispanic; american mainstream media; immigration; U.S. news magazines; misconception